XML and Oracle9i Release 2 Oracle has a strong contender in the XML database market. - Cowan, William (XML journal :the ultimate enterprise resource.)
With Oracle9i RDBMS Release 2, Oracle has moved further along on the road to a more complete implementation of XML in its database. This release also marks, I believe, one of Oracle's most significant uses of the object-relational capabilities of the database. By combining these capabilities with XML and adhering to W3C standards, Oracle has in the current release a strong contender in the XML-enabled database market and without losing the relational capabilities of the database. By combining these capabilities with XML and adhering to W3C standards, Oracle has in the current release a strong contender in the XML-enabled database market...and without losing the relational capabilities of the database.